Interfacial challenges and progress for inorganic all-solid-state lithium batteries. (10th September 2018) - Xu, R.C.; Xia, X.H.; Zhang, S.Z.; Xie, D.; Wang, X.L.; Tu, J.P.
Abstract: All-solid-state lithium batteries (ASSLIBs) employed inorganic solid electrolytes are attracting increasing interest for electrochemical energy storage devices due to their advantages of high safety, high energy density, wide operating temperature range and long cycle life. However, the large interfacial resistance originated from the insufficient solid-solid contact at electrolyte/electrode interface hinders the development of all-solid-state batteries. In addition, the interfacial compatibility and stability also greatly affect the electrochemical performance of batteries. This review summarizes the challenges and progress for the studies of interface problems in ASSLIBs. Based on the review, we attempt to propose alternative approaches to the issue and prospective developments of ASSLIBs. Highlights: All-solid-state cells with inorganic electrolytes suffer from interface problems. Challenges and recent progress of the interface problems are summarized. Great effort is needed to enable solid batteries as viable energy storages.